A combination of the finite element analysis and experimental indentation via the cornea. (February 2019) - Karimi, Alireza; Razaghi, Reza; Sera, Toshihiro; Kudo, Susumu
Abstract: The purpose of this study was to perform a set of experimental indentation test to certify our proposed eye model enables to have a better deformation assessment for the eye globe under the indentation load compared to other eye models. To do that, twenty-four enucleated human globes were removed from the cadavers. A screw at 5 different loading rates indented to the eye globes and the resulting macroscopic force-displacement as a result of the deformation in the apex of the cornea was measured. The experimental results revealed significantly higher stiffness, elastic modulus, and maximum force for the globe at higher loading rates (50 and 100 mm/min) (n = 4 globes, p  < 0.05, post hoc Scheffe method) compared to the lower ones (5, 10, and 20 mm/min). The mean stiffness, elastic modulus as well as the mean maximum force of 1.64 ± 0.38 N/mm, 303.40 ± 111.10 kPa, and 53.88 ± 17.63 N (Mean ± SD) were observed for the eye globes under all loading rates, respectively. Our eye model due to incorporating the anterior (cornea, aqueous body, and iris) and posterior (sclera, retina, and vitreous body) components showed a good agreement with force-displacement diagrams compared to that of the experimental results not only at lower but also at higher loading rates.